Serum Vitamin D Insufficiency in Hospitalized Full-Term Neonates at a Tertiary Hospital in Eastern China - Wang, Huawei; Du, Yiming; Wu, Zhixin; Geng, Haifeng; Zhu, Xueping; Zhu, Xiaoli (Frontiers in Pediatrics, 2022)
Objective This study explored the status of serum vitamin D in hospitalized full-term neonates at a tertiary hospital in eastern China. Methods A prospective study was conducted among 471 hospitalized full-term neonates at the Children's Hospital of Soochow University between January 1 and June 20, 2020. Perinatal clinical data, serum 25-hydroxyvitamin D (25(OH)D3), laboratory examinations, serum calcium levels, and immune function were obtained and analyzed. We explored and analyzed the risk factors for vitamin D insufficiency or deficiency, and we also attempted to determine correlations between vitamin D and its influence on immunity. Results The mean serum 25(OH)D3 was 33.65±6.07ng/ml.The prevalence of vitamin D insufficiency was 28.24%,vitamin D sufficiency was 71.76%, there was no vitamin D deficiency. The serum 25-(OH)D3 in singleton neonate was higher than twins or multiple infants (t = −10.918, P = 0.000). The serum 25-(OH)D3 were higher in neonates who born in spring and summer than in winter (H = 13.443, P = 0.001). The serum 25-(OH)D3 in appropriate for gestational age (AGA) and large for gestational age (LGA) neonates were higher than small for gestational age (SGA) (H = 7.686, P = 0.021). The serum 25-(OH)D3 were higher in neonates whose mothers had no underlying diseases than those with certain immunological and infectious diseases (F = 12.417, P = 0.000). The serum 25-(OH)D3 in neonates whose mothers had none or one perinatal complication were higher than those with two or more (F = 13.299, P = 0.000). The neonates with eosinophils ≤5% or normal platelet counts or serum Ca++ ≥0.9 mmol/L have higher serum 25-(OH)D3. Neonates born in winter were at risk for vitamin D insufficiency, and the incidence of infectious pneumonia, sepsis, cytomegalovirus infection, and hypocalcemia in the vitamin D insufficiency group were higher than sufficiency group (P < 0.05). The serum CD3+, CD3+CD4+, and IgA levels in vitamin D sufficiency neonates were significantly higher than those in insufficiency group (P < 0.05). Conclusion The prevalence of vitamin D insufficiency was 28.24%, and birth in winter was a risk factor for vitamin D insufficiency in hospitalized full-term neonates in Suzhou area. Neonates with infectious pneumonia, sepsis, cytomegalovirus infection, and hypocalcemia exhibited a high risk of vitamin D insufficiency. The serum CD3+, CD3+CD4+, and IgA levels in neonates with vitamin D insufficiency were lower.